WATERCOLOUR LAKES & RIVERS : Start to paint with 3 colours, 3 brushes and 9 easy projects - Coates, Stephen, 1960- (Tunbridge Wells : Search Press, 2019)
With 3 colours, 3 brushes and this practical advice, you can start painting water scenes in watercolour with just 9 projects. Even if you have never picked up a paintbrush before, professional watercolour teacher and artist, Stephen Coates, shows you how to paint convincing water scenes in watercolour using just three brushes, three colours, a plastic palette and a watercolour pad. Only students' range watercolour paints are used, yet from these Stephen shows you how to paint nine realistic watercolour scenes. There is no off-putting color theory or long-winded mixing information, but a practical absolute beginner's course that shows the three colours in action. You need only three affordable brushes: a hake and a no. 8 and no. 2 rounds in a synthetic range, to achieve all of the paintings shown. Build your skills through nine easy exercises, starting from the simplest of scenes, resulting in paintings of rivers and lakes you'll be proud of. There are step-by-step photographs for each project, meaning clear instruction and advice throughout, and handy tips and jargon busters appear alongside the steps for short and simple answers to your watercolour woes. Each of Stephen's finished paintings are shown at full size for easy reference, which you can even use to trace from for a stress-free painting experience - a helpful how-to-trace section at the back of the book shows you how to do this too, with Stephen's friendly instruction
Keywords: Watercolor painting -- Technique; Rivers in art; Lakes in art